Practices of Implementing Divorce Case Mediation in Yogyakarta Religious Courts Review of Positive Law and Maqasid Syariah - Sahril Fadli; Rafi Pradipa; Relisa; Nurchamidah; Hartiningsih (al-Afkar, Journal For Islamic Studies, 2025)
This study examines and explores the effectiveness of Mediation Settlement in Divorce Cases at the Yogyakarta City Religious Court or PAY. The research method is based on the research object in the form of a cumulative study of divorce cases at the Yogyakarta Religious Court where case tracing and decisions and interviews with several judges are the data sources. From January to December 2023, out of 764 cases recorded, only 162 were mediated, of which 55 divorce cases were successful. PAY has carried out the mediation process in accordance with Supreme Court Regulation or PERMA Number 1 of 2016 concerning Mediation Procedures in Court and uses PERMA as a reference in applying mediation it is evident that Maqasid Syariah can function as a guide for Yogtakarta Religious Court mediators in the process of achieving reconciliation between the parties involved in the dispute.